Gender and Socioeconomic Disparities in Global Burden of Epilepsy: An Analysis of Time Trends From 1990 to 2017 - Hu, Yin; Shan, Yi; Du, Qiang; Ding, Yao; Shen, Chunhong; Wang, Shuang; Ding, Meiping; Xu, Yufeng (Frontiers in Neurology, 2021)
Objective: To investigate the gender and socioeconomic disparities in the global burden of epilepsy by prevalence and disability-adjusted life-years (DALYs). Methods: The global, regional, and national gender-specific prevalence and DALYs caused by epilepsy by year and age were extracted from Global Burden of Disease (GBD) Study 2017. The Gini coefficient and concentration index (CI) were calculated to demonstrate the trends in between-country inequality in the epilepsy burden from 1990 to 2017. Paired Wilcoxon signed rank test, Pearson correlation, and linear regression analyses were performed to analyze the association of gender disparity in epilepsy and Socio-demographic Index (SDI). Results: The DALYs number of epilepsy increased from 1990 to 2017 by 13.8%, whereas age-standardized DALY rates showed a substantial reduction (16.1%). Men had a higher epilepsy burden than women of the same period. The epilepsy burden appeared to be higher in countries with lower socioeconomic development (CI < 0). The Gini coefficient decreased from 0.273 in 1995 to 0.259 in 2017, representing a decline in the between-country gap. Age-standardized prevalence and DALY rates of men were higher than those of women in each SDI-based country group (p < 0.0001). Male-minus-female difference (r = -0.5100, p < 0.0001) and male-to-female ratio (r = -0.3087, p < 0.0001) of age-standardized DALY rates were negatively correlated with SDI. Conclusion: Although global health care of epilepsy is in progress, the epilepsy burden was concentrated in males and developing countries. Our findings highlight the importance of formulating gender-sensitive health policies and providing more services in developing countries.